FEN BİLİMLERİ DERS KİTABINDA BULUNAN KİMYA ÜNİTELERİNDEKİ BÖLÜM SONU SORULARININ YENİLENMİŞ BLOOM TAKSONOMİSİNE GÖRE İNCELENMESİ - SİNCAR, BURHAN (Fırat Üniveristesi, 2022)
Bu araştırmada, 5, 6, 7 ve 8. sınıf fen bilimleri ders kitaplarında bulunan kimya ünitelerindeki bölüm sonu soruları yenilenmiş Bloom taksonomisine göre irdelenmiştir. Araştırmada nitel araştırma yöntemlerinden biri olan doküman analizi yöntemi kullanılmıştır. Toplam 239 soru, yenilenmiş Bloom taksonomisinin bilişsel süreç boyutu esas alınarak sınıflandırılmıştır. Elde edilen veriler yüzde ve frekans olarak tablolarda sunulmuştur. Araştırma sonucunda şu hususlar tespit edilmilmiştir: Üst düzey becerileri ölçen soruların yüzdesi, alt düzey becerileri ölçen soruların yüzdesinden oldukça düşüktür. Alt düzey bilişsel alan basamaklarında bulunan sorular genellikle hatırlama basamağına ait sorulardır. Uygulama basamağına ait soru oranı çok düşüktür. Üstbilişsel basamaklarda ise en fazla soru çözümleme basamağına ait sorulardır. Yaratma basamağına ait soruların yüzdesi oldukça düşüktür. Değerlendirme basamağına ait soru bulunmamaktadır. Anahtar Kelimeler: Fen Eğitimi, Yenilenmiş Bloom Taksonomisi, Soru Analizi

In this research, the end-of-chapter questions in the chemistry units in the 5th, 6th, 7th and 8th grade science textbooks were examined according to the revised Bloom's taxonomy. The document analysis method, which is one of the qualitative research methods, was used in the research. A total of 239 questions were classified based on the cognitive process dimension of the revised Bloom's taxonomy. Obtained data are presented in tables as percentage and frequency. As a result of the research, the following points were determined: The percentage of questions measuring high-level skills is considerably lower than the percentage of questions measuring low-level skills. The questions found in the lower level cognitive domain steps are generally questions belonging to the remembering step. The rate of questions for the application step is very low. In the metacognitive steps, the most questions are the questions belonging to the analysis step. The percentage of questions related to the creation step is quite low. There are no questions related to the evaluation step. Keywords: Science Education, Revised Bloom's Taxonomy, Question Analysis
Examination of the end-of-chapter questions in the chemistry units found in the science textbook according to the Revised Bloom's Taxonomy
Keywords: Eğitim ve Öğretim